Evaluation of Power Quality in a Residential Photovoltaic System: Case Study - Sousa Santos, Vladimir; Ospino Castro, Adalberto; Balbis Morejón, Milén; Martinez-Cueto, Carol; Rondón Rodríguez, Carlos A. (International Journal of Energy Economics and Policy, 2025)
This paper evaluates the power quality in a residential photovoltaic system in Colombia. Power quality parameters were monitored in a residence in Barranquilla with a 4.44 kW system connected to the grid, analyzing its behavior over time and comparing it with regulatory limits. Graphical and statistical analysis tools were used to identify deviations and problems in the network based on current regulations. The results show a voltage unbalance reaching 9.84% and a current unbalance of up to 147.7%, with a total demand distortion of up to 17.1% and a k-factor >70%. These results show high unbalance and harmonics in the supply source, affecting network stability, efficiency, and equipment life. The research confirms that the injection of energy from photovoltaic systems can affect power quality in low-voltage networks, highlighting the need for mitigation strategies. The implementation of advanced controls in inverters, active filters, and FACTS devices is proposed, along with strengthening the regulation of harmonic distortion and load balancing in residential networks. Given the accelerated growth of photovoltaic generation in Colombia, it is essential to evaluate its long-term impact to ensure the stability of the electrical system and maximize the benefits of distributed generation in the country.